Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
[tex]y = -\frac{2}{3}x + 490[/tex]
gradient = = [tex]-\frac{2}{3}[/tex]
y-intercept = [tex]490[/tex]
Step-by-step explanation:
• The slope-intercept form of an equation takes the general form:
[tex]\boxed{y = mx + c}[/tex],
where:
m = slope,
c = y-intercept.
• We are given the equation:
[tex]2x + 3y = 1470[/tex]
To change this into the slope-intercept form, we must make y the subject:
[tex]3y = -2x + 1470[/tex] [subtract [tex]2x[/tex] from both sides]
⇒ [tex]y = -\frac{2}{3}x + \frac{1479}{3}[/tex] [divide both sides by 3]
⇒ [tex]y = -\frac{2}{3}x + 490[/tex]
• Comparing this equation with the general form equation, we see that:
m = [tex]-\frac{2}{3}[/tex]
c = [tex]490[/tex].
This means that the gradient is [tex]\bf -\frac{2}{3}[/tex], and the y-intercept is [tex]\bf 490[/tex].
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.